Material didáctico sobre cuidado bucal para niños nasa páez productos para la educación en salud con enfoque inclusivo dirigidos a niños de 6 a 12 años (2021)
This document presents the proposal of educational material for learning oral health care, aimed at boys and girls between 6 and 12 years of age, and which seeks an inclusive approach through cultural appropriation by the indigenous community. Nasa Paez. This product seeks to provide means for health education in the Colombian territory. For this, it seeks to maintain consistency with the educational intentions of pediatric dentistry, the general culture of the Nasa Páez community, and with the logical construction of material to teach about health and create dynamic learning and play experiences.